A method for testing the pore size distribution of hemodialysis hollow fiber membranes

By using a variety of molecular measuring ethylene glycol and ultraviolet iodine liquid color rendering method, the pore diameter distribution of hemodialysis membranes is used to solve the problem of insufficient pore diameter distribution test accuracy in existing technologies, and higher accuracy and stable test results.

CN117129401BActive Publication Date: 2025-01-28JIANGXI SANXIN MEDTEC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311119552.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-01
Publication Date
2025-01-28
Estimated Expiration
2043-09-01

AI Technical Summary

Technical Problem

The existing hemodialysis hollow fiber membrane pore size distribution testing methods have problems such as insufficient accuracy and large data, especially when the concentration of the simulation solution changes before and after the dialysis cycle, which affects the accuracy of the pore size distribution results.

Method used

A variety of molecular measuring polyethylene glycol is configured with different concentration solutions, combined with ultraviolet iodine liquid color rendering method and ultraviolet optical light meter, accurately determine the concentration of the analog liquid and dialysis solution before and after the dialysis, and analyze the blood through the analysis of the interception rate and the diameter of the molecular diameter to establish blood. The dialysis membrane pore diameter pair of normal distribution probability density function, calculate the pore diameter distribution.

Benefits of technology

A more accurate and stable test of the distribution of hemodialysis membrane pores, reducing errors, improving the accuracy and reliability of the test results, and avoiding the impact of non -passing pores and twists and turns on the test results.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117129401B_ABST
    Figure CN117129401B_ABST
Patent Text Reader

Abstract

The invention discloses a test method for the pore size distribution of a hemodialysis hollow fiber membrane. The test method first uses an ultraviolet spectrophotometer to draw a "concentration-ultraviolet absorbance" linear regression fitting curve of polyethylene glycol (PEG) solutions with different concentrations and different molecular weights; PEG simulated solutions with different molecular weights are passed through a dialysis membrane to obtain a dialysis fluid, and the concentrations of the PEG simulated solutions with different molecular weights and the dialysis fluid are calculated using an optimal determination coefficient linear regression curve to further calculate the retention rate; Python is used to construct a relationship between the retention rate and the pore size, and finally the dialysis membrane pore size distribution is obtained in combination with Matlab fitting calculation. The invention can quickly measure the pore size distribution of the hemodialysis membrane, and its measurement data has high accuracy, a simple principle, and strong practicality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hemodialysis membrane characterization, and in particular relates to a method for testing the pore size distribution of a hemodialysis hollow fiber membrane. Background Art

[0002] Hemodialysis is currently the most widely used and most effective method for treating uremia. As an in vitro device, it has the function of simulating renal function and is referred to as an "artificial kidney". Dialysis follows the principle of solute diffusion and follows three basic processes: diffusion, ultrafiltration and adsorption. The pore size and pore size distribution data of hemodialysis hollow fiber membranes are of great significance. However, there are many methods for testing pore size and pore size distribution, there is no unified standard, and the test methods vary due to differences in the characteristics of the sample materials. Therefore, it is of practical significance to find a stable, accurate and efficient pore size distribution test method.

[0003] There are many methods for testing the pore size and pore size distribution of membranes. For example, direct observation by electron microscopy and atomic force microscopy; and indirect determination by mercury intrusion, bubble pressure, filtration rate, gas adsorption and molecular weight cutoff methods. For hemodialysis hollow fiber membranes, the pore size is a curved pore size, about less than 10nm. Although scanning electron microscopy (SEM) and atomic force microscopy (AFM) can directly observe the surface morphology and pore size of the sample, they ignore the influence of blind holes and tortuosity, and it is difficult to analyze the pore size distribution test results, which often leads to biased test results. Therefore, the direct measurement method cannot determine the pore size distribution. The mercury intrusion method and bubble pressure method use a large pressure for membranes with smaller pore sizes, and the hollow fiber membrane itself is made of a soft material. Excessive pressure can easily deform the pore size of the membrane, thereby affecting the accuracy of the results. Gas adsorption method (BET) The gas adsorption method is a test method that calculates the pore size distribution of the membrane based on the Kelvin equation according to the various mechanisms of gas adsorption on porous materials. It is currently commonly used for pore size distribution tests of mesoporous materials (50nm). In the micropore range, after less than 10nm, the results are less accurate than those of mesoporous materials. The molecular weight cut-off method can obtain the pore size distribution by adding software data processing after testing the cut-off amount. Therefore, for this sample, the molecular weight cut-off method is first considered to determine the pore size distribution.

[0004] For example, patent CN 106596376 A discloses a method for testing the pore size distribution of a hemodialysis membrane. The method for testing the concentration of the simulated fluid and the dialysate is to use a light scattering method, but the specific test method is not described in detail, such as the specific concentration of the simulated fluid configuration, and the concentration change of the simulated fluid before and after the dialysis cycle is stabilized is not considered, which may affect the final pore size distribution result. Summary of the invention

[0005] The purpose of the present invention is to provide a testing method for the pore size distribution of hemodialysis hollow fiber membranes, aiming to solve the shortcomings of the above-mentioned pore size distribution, and to more accurately derive the specific concentrations of simulated fluid and dialysate before and after dialysis, so as to obtain more stable and accurate pore size distribution results.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] The present invention provides a method for testing the pore size distribution of a hemodialysis hollow fiber membrane, comprising:

[0008] S1: Prepare solutions of different concentrations using polyethylene glycols of various molecular weights, and use the iodine solution colorimetric method. For small molecular weight PEG, use barium chloride solution to prepare iodine solution colorimetric solution, and for large molecular weight PEG, use boric acid solution to prepare iodine solution colorimetric solution, to obtain PEG simulation solutions of different molecular weights; use an ultraviolet spectrophotometer to measure the absorbance of the iodine solution colorimetric solution, and draw a "concentration-absorbance" linear regression fitting curve at different wavelengths, and take the "concentration-absorbance" linear regression curve of the wavelength with the optimal determination coefficient R2 curve as the standard curve;

[0009] S2: Polyethylene glycol solute is dissolved in pure water as the simulated fluid, and the dialysate is obtained after filtering through a hemodialysis membrane;

[0010] S3: Use a UV spectrophotometer to test the absorbance of the different molecular weight PEG simulation solutions in S1 and the dialysate in S2, and use the standard curve to calculate the solution concentration;

[0011] S4: Calculate the retention rate of the dialysate and the PEG simulation fluids with different molecular weights corresponding to the solute molecular weight according to equation 1:

[0012]

[0013] Where R is the retention rate, C p and C f are the concentrations of dialysate and simulated solution of PEG with different molecular weights;

[0014] S5: Calculate the molecular Stokes radius r of the corresponding solute molecular weight of the PEG dialysate and the simulated fluid with different molecular weights according to equation 2:

[0015] r = 16.73 × 10 -12 ×M 0.557 (2)

[0016] Where r is the molecular radius of the solute, and M is the molecular weight of the solute;

[0017] S6: Take the molecular diameter d of the solute particles of PEG dialysate and simulated solution with different molecular weights sThe natural logarithm of ln(ds) is normalized to ln(d sn ), limiting the range of the logarithmic molecular diameter to the interval [0,1]:

[0018]

[0019] Among them, d s_max and d s_min are the maximum molecular diameter and the minimum molecular diameter, respectively;

[0020] The mapping relationship between the retention rate and the normalized logarithmic molecular diameter is obtained by the smooth cubic spline interpolation method in equation 4:

[0021]

[0022] Among them, R c is the actual interception rate, m is the number of nodes of the smooth cubic spline interpolation, a (m-1) , b (m-1) 、c (m-1) and d (m-1) are the coefficients of the m-1th segment of cubic spline curve expression;

[0023] The log-normal distribution probability density function and cumulative distribution function of the hemodialysis membrane pore size dp are established, see equations 5 and 6:

[0024]

[0025] Among them, d p is the pore diameter of the hemodialysis membrane, μ s is the average geometric diameter of the solute when R = 50%, lnσ g It is about lnμ s The geometric standard deviation is defined as ln(d s ) ratio:

[0026]

[0027] Among them, d s is the solute diameter, μ s is the geometric mean diameter of the solute when R = 50%, σ g It's about μ s The geometric standard deviation is defined as the value of R = 84.13% and 50% d s The ratio of

[0028] S7: The measured retention rate, molecular weight and membrane pore size d p The cumulative distribution function is calculated from the variation range data to obtain the pore size distribution.

[0029] Preferably, the molecular weight of polyethylene glycol in the small molecular weight PEG is 300-800Da, the molecular weight of polyethylene glycol in the large molecular weight PEG is 1k-20k Da, the concentration of PEG of different molecular weights is 100mg / L, and the concentration range in the polyethylene glycol "concentration-absorbance" standard curve is 0-20mg / L.

[0030] Preferably, the temperature of the pure water and filtration in S2 is set to 20-30°C.

[0031] Preferably, the experimental cycle stabilization time of dialysis in S2 is 1 hour, the flow rate is 100 mL / min, and the flow rate when collecting dialysate after the cycle is stabilized is 200 mL / min.

[0032] Preferably, in S5, the solute molecular weight test method is gel permeation chromatography.

[0033] Preferably, in S6, when R=84.13% is calculated in equation 4, the normalized logarithmic diameter of the particle molecule ln(d s_n1 ); Calculate the normalized logarithmic diameter of the particle molecule when R = 50% ln (d s_n2 )(ln(μ s_n )); then ln(d s_n1 ) and log(d s_n2 ) is reverse normalized to obtain the logarithmic diameter of the particle molecule when R = 84.13% (d s_1 ) and the logarithmic diameter of the particle molecule when R = 50% (d s_2 )(ln(μ s )).

[0034] Preferably, the analysis software for smooth cubic spline interpolation in S6 is Python, and the software for fitting the PEG standard curve and performing nonlinear fitting of the corresponding pore size distribution function is Matlab.

[0035] Technical effects and advantages of the present invention: Compared with the prior art, the present invention provides a method for testing the pore size distribution of hemodialysis hollow fiber membranes, which has the following advantages:

[0036] In the present invention, since the concentration of the simulated fluid will change before and after the dialysis cycle, the ultraviolet iodine solution colorimetric method is used to accurately test the concentrations of the simulated fluid and the dialysate before and after the dialysis. Therefore, the test results obtained by the test method of the present invention are accurate, the error is small, and the method is simple. In addition, when testing the pore size distribution of the dialysis membrane, the test method of the present invention is based on the solute filtration measurement basis. Compared with other methods such as the electron microscopy method, the data fluctuation is small, the accuracy is high, and the pore size distribution of the hemodialysis membrane can be quickly determined. The measurement data has high accuracy, a simple principle, and strong practicality. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 The present invention is a "concentration-absorbance" linear regression fitting curve drawn according to the absorbance of a polyethylene glycol solution with a molecular weight of 4000Da at a wavelength of 510nm at different concentrations;

[0038] Figure 2 is a pore size distribution curve graph obtained by the first parallel experiment of the polyethersulfone hemodialysis membrane in Example 1 of the present invention;

[0039] Figure 3 is a pore size distribution curve graph obtained by parallel experiments of the polyethersulfone hemodialysis membrane in Example 1 of the present invention;

[0040] Figure 4 This is another pore size distribution curve obtained by a parallel experiment of the polyethersulfone hemodialysis membrane in Example 1 of the present invention. DETAILED DESCRIPTION

[0041] The following will be combined with the accompanying drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. The specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0042] The present invention provides a method for testing the pore size distribution of a hemodialysis hollow fiber membrane, comprising:

[0043] S1: Prepare solutions of different concentrations using polyethylene glycols of various molecular weights, and use the iodine solution colorimetric method. For small molecular weight PEG, use barium chloride solution to prepare iodine solution colorimetric solution, and for large molecular weight PEG, use boric acid solution to prepare iodine solution colorimetric solution, to obtain PEG simulation solutions of different molecular weights; use an ultraviolet spectrophotometer to measure the absorbance of the iodine solution colorimetric solution, and draw a "concentration-absorbance" linear regression fitting curve at different wavelengths, and take the "concentration-absorbance" linear regression curve of the wavelength with the optimal determination coefficient R2 curve as the standard curve;

[0044] Specifically, the molecular weight of polyethylene glycol in the small molecular weight PEG is 300-800 Da, the molecular weight of polyethylene glycol in the large molecular weight PEG is 1k-20k Da, the concentration of PEG of different molecular weights is 100 mg / L, and the concentration range in the polyethylene glycol "concentration-absorbance" standard curve is 0-20 mg / L.

[0045] S2: Polyethylene glycol solute was dissolved in pure water as the simulated liquid, and the dialysate was obtained after filtering through the hemodialysis membrane; the temperature of the pure water and the filtration was set at 20-30°C; the experimental cycle stabilization time of the dialysis was 1h, the flow rate was 100mL / min, and the flow rate when collecting the dialysate after the cycle was stable was 200mL / min.

[0046] S3: Use a UV spectrophotometer to test the absorbance of the different molecular weight PEG simulation solutions in S1 and the dialysate in S2, and use the standard curve to calculate the solution concentration;

[0047] S4: Calculate the retention rate of the dialysate and the PEG simulation fluids with different molecular weights corresponding to the solute molecular weight according to equation 1:

[0048]

[0049] Where R is the retention rate, C p and C f are the concentrations of dialysate and simulated solution of PEG with different molecular weights;

[0050] S5: Calculate the molecular Stokes radius r of the corresponding solute molecular weight of the PEG dialysate and the simulated fluid with different molecular weights according to equation 2:

[0051] r = 16.73 × 10 -12 ×M 0.557 (2)

[0052] Where r is the molecular radius of the solute and M is the molecular weight of the solute.

[0053] Furthermore, the solute molecular weight test method is gel permeation chromatography.

[0054] S6: Take the molecular diameter d of the solute particles of PEG dialysate and simulated solution with different molecular weights s The natural logarithm of ln(ds) is normalized to ln(d sn ), limiting the range of the logarithmic molecular diameter to the interval [0,1]:

[0055]

[0056] Among them, d s_max and d s_min are the maximum molecular diameter and the minimum molecular diameter, respectively;

[0057] The mapping relationship between the retention rate and the normalized logarithmic molecular diameter is obtained by the smooth cubic spline interpolation method in equation 4:

[0058]

[0059] Among them, R c is the actual interception rate, m is the number of nodes of the smooth cubic spline interpolation, a (m-1) , b (m-1) 、c (m-1) and d (m-1) are the coefficients of the m-1th segment of cubic spline curve expression;

[0060] The log-normal distribution probability density function and cumulative distribution function of the hemodialysis membrane pore size dp are established, see equations 5 and 6:

[0061]

[0062] Among them, d p is the pore diameter of the hemodialysis membrane, μ s is the average geometric diameter of the solute when R = 50%, lnσ g It is about lnμ s The geometric standard deviation is defined as ln(d s ) ratio:

[0063]

[0064] Among them, d s is the solute diameter, μ s is the geometric mean diameter of the solute when R = 50%, σ g It's about μ s The geometric standard deviation is defined as the value of R = 84.13% and 50% d s The ratio of

[0065] Specifically, when R=84.13% is calculated in equation 4, the normalized logarithmic diameter of the particle molecule ln(d s_n1 ); Calculate the normalized logarithmic diameter of the particle molecule when R = 50% ln (d s_n2 )(ln(μ s_n )); then ln(d s_n1 ) and log(d s_n2 ) is reverse normalized to obtain the logarithmic diameter of the particle molecule when R = 84.13% (d s_1 ) and the logarithmic diameter of the particle molecule when R = 50% (d s_2 )(ln(μ s ));

[0066] In addition, the analysis software for smooth cubic spline interpolation was Python, and the software for fitting the PEG standard curve and the nonlinear fitting of the corresponding pore size distribution function was Matlab.

[0067] S7: The measured retention rate, molecular weight and membrane pore size d p The cumulative distribution function is calculated from the variation range data to obtain the pore size distribution.

[0068] In this embodiment, since the concentration of the simulated liquid changes before and after the dialysis cycle, the ultraviolet iodine solution colorimetric method is used to accurately test the concentrations of the simulated liquid and the dialysate before and after dialysis. Therefore, the test results obtained by the test method of the present invention are accurate, the error is small, and the method is simple. In addition, when testing the pore size distribution of the dialysis membrane, the test method of the present invention is based on the solute filtration measurement. Compared with other methods such as the electron microscopy method, it has the advantages of small data fluctuation, high accuracy, and the ability to avoid the influence of non-through holes on the test results, etc., which provides a practical and convenient performance evaluation method for the research and use of hemodialysis membranes.

[0069] Example 1

[0070] Take a certain brand of polyethersulfone hemodialyzer on the market. Use polyethylene glycol (PEG) with different molecular weights as test materials, and the molecular weights of polyethylene glycol are 300, 400, 600, 800, 1k, 2k, 4k, 6k, 8k, 10k, and 20k Da. Prepare solutions with concentrations of 0, 5, 10, 15, and 20 mg / L for each polyethylene glycol with different molecular weights.

[0071] An iodine solution color developing solution is prepared, wherein a solution with a PEG molecular weight of 300-800Da is added with 1.2mL of a 5wt% barium chloride solution and 1mL of a 0.1mol / L iodine solution in a 10mL volumetric flask and the volume is adjusted; a solution with a PEG molecular weight of 1k-20kDa is added with 15mL of a 0.5mol / L boric acid solution and 2mL of a 0.1mol / L iodine solution in a 100mL volumetric flask and the volume is adjusted.

[0072] The absorbance of the iodine solution was determined by ultraviolet spectrophotometer, and the "concentration-absorbance" linear regression fitting curve was plotted at different wavelengths. The "concentration-absorbance" linear regression curve at the wavelength of the optimal determination coefficient (R2) curve was taken as the standard curve.

[0073] Prepare simulated polyethylene glycol solutions of various molecular weights at a concentration of 100 mg / L. The simulated solutions are filtered through a polyethersulfone hemodialyzer with an experimental cycle stabilization time of 1 h and a flow rate of 100 mL / min to obtain filtrate.

[0074] The absorbance of the simulated solution and the filtrate after circulation was measured by an ultraviolet spectrophotometer, and the concentration of the solution was calculated using the "concentration-absorbance" standard curve.

[0075] The obtained concentration was used to calculate the retention rate using the retention rate formula.

[0076] The molecular weight of the solutes was determined by gel permeation chromatography and the Stokes radius was calculated.

[0077] Python and Matlab were used to calculate the mean and standard deviation of the pore size distribution, and the fitting results were used to obtain the pore size distribution.

[0078] like Figure 1 As shown, Figure 1 The “concentration-absorbance” linear regression fitting curve is drawn based on the absorbance of polyethylene glycol solution with a molecular weight of 4000Da at a wavelength of 510nm at different concentrations. Figure 2 This is the pore size distribution curve of the hemodialysis membrane measured in the first parallel experiment. Figure 3 Figure 4 It is the pore size obtained by the parallel experiment. According to its pore size distribution, the pore size distribution of the hemodialysis membrane is mainly concentrated between 8 and 9 nm.

[0079] Comparative Example 1

[0080] The same high-pass hemodialyzer as in Example 1 was selected, and its pore size distribution was tested using field emission scanning electron microscopy.

[0081] In the experiment, a section of membrane filament was cut and fixed on the electron microscope sample stage. After drying, it was sprayed with gold and electron microscope pictures of the inner and outer surfaces of the hollow fiber were taken.

[0082] It is found that the pore size is too large, which indicates that the electron microscopy test ignores the influence of tortuosity and non-through holes, or the shape of the inner and outer through holes of the hemodialysis membrane is dumbbell-shaped, and the electron microscopy method captures the actual pore size of the inner and outer surfaces, while the actual through hole in the middle is very small, resulting in a larger test result. The present invention is based on a filtration experiment, which tests the pore size distribution of effective filtration through holes, and the test result accuracy is relatively higher.

[0083] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for testing the pore size distribution of a hemodialysis hollow fiber membrane, characterized in that: include: S1: Use polyethylene glycol of various molecular weights to prepare solutions of different concentrations, and use the iodine solution colorimetric method. For small molecular weight PEG, use barium chloride solution to prepare iodine solution colorimetric solution, and for large molecular weight PEG, use boric acid solution to prepare iodine solution colorimetric solution, to obtain PEG simulation solutions of different molecular weights; use an ultraviolet spectrophotometer to measure the absorbance of the iodine solution colorimetric solution, and draw a "concentration-absorbance" linear regression fitting curve at different wavelengths, and take the "concentration-absorbance" linear regression curve of the wavelength with the optimal determination coefficient R2 curve as the standard curve; S2: Polyethylene glycol solute is dissolved in pure water as the simulated fluid, and the dialysate is obtained after filtering through a hemodialysis membrane; S3: Use a UV spectrophotometer to test the absorbance of the different molecular weight PEG simulation solutions in S1 and the dialysate in S2, and use the standard curve to calculate the solution concentration; S4: Calculate the retention rate of the dialysate and the PEG simulation fluids with different molecular weights corresponding to the solute molecular weight according to equation 1: Where R is the retention rate, C p and C f are the concentrations of dialysate and simulated solution of PEG with different molecular weights; S5: Calculate the molecular Stokes radius r of the corresponding solute molecular weight of the PEG dialysate and the simulated fluid with different molecular weights according to equation 2: r=16.73×10 -12 ×M 0.557 (2) Where r is the molecular radius of the solute, and M is the molecular weight of the solute; S6: Take the molecular diameter d of the solute particles of PEG dialysate and simulated solution with different molecular weights s The natural logarithm of ln(ds) is normalized according to equation 3: Limit the range of the logarithmic molecular diameter to the interval [0,1]: Among them, d s_max and d s_min are the maximum molecular diameter and the minimum molecular diameter, respectively; The mapping relationship between the retention rate and the normalized logarithmic molecular diameter is obtained by the smooth cubic spline interpolation method in equation 4: ln(d sn )= Among them, R c is the actual interception rate, m is the number of nodes of the smooth cubic spline interpolation, a (m-1) , b (m-1) 、c (m-1) and d (m-1) are the coefficients of the m-1th segment of cubic spline curve expression; The log-normal distribution probability density function and cumulative distribution function of the hemodialysis membrane pore size dp are established, see equations 5 and 6: Among them, d p is the pore diameter of the hemodialysis membrane, μ s is the average geometric diameter of the solute when R = 50%, lnσ g It is about lnμ s The geometric standard deviation is defined as ln(d s ) ratio: Among them, d s is the solute diameter, μ s is the geometric mean diameter of the solute when R = 50%, σ g It's about μ s The geometric standard deviation is defined as the value of R = 84.13% and 50% d s The ratio of S7: The measured retention rate, molecular weight and membrane pore size d p The cumulative distribution function is calculated from the variation range data to obtain the pore size distribution.

2. The method for testing the pore size distribution of a hemodialysis hollow fiber membrane according to claim 1, characterized in that: The molecular weight of polyethylene glycol in the small molecular weight PEG is 300-800Da, the molecular weight of polyethylene glycol in the large molecular weight PEG is 1k-20k Da, the concentration of PEG with different molecular weights is 100mg / L, and the concentration range in the polyethylene glycol "concentration-absorbance" standard curve is 0-20mg / L.

3. The method for testing the pore size distribution of a hemodialysis hollow fiber membrane according to claim 1, characterized in that: The temperature of pure water and filtration in S2 is set to 20-30°C.

4. The method for testing the pore size distribution of a hemodialysis hollow fiber membrane according to claim 3, characterized in that: The experimental cycle stabilization time of dialysis in S2 was 1 h, the flow rate was 100 mL / min, and the flow rate was 200 mL / min when the dialysate was collected after the cycle was stabilized.

5. The method for testing the pore size distribution of a hemodialysis hollow fiber membrane according to claim 1, characterized in that: In S5, the solute molecular weight test method is gel permeation chromatography.

6. The method for testing the pore size distribution of a hemodialysis hollow fiber membrane according to claim 1, characterized in that: In S6, when R=84.13% is calculated in equation 4, the normalized logarithmic diameter of the particle molecule ln(d s_n1 ); Calculate the normalized logarithmic diameter of the particle molecule when R = 50% ln (d s_n2 )(ln(μ s_n )); then ln(d s_n1 ) and log(d s_n2 ) was reverse normalized to obtain the logarithmic diameter of the particle molecule when R = 84.13% (d s_1 ) and the logarithmic diameter of the particle molecule when R = 50% (d s_2 )(ln(μ s )).

7. The method for testing the pore size distribution of a hemodialysis hollow fiber membrane according to claim 6, characterized in that: The analysis software for smooth cubic spline interpolation in S6 was Python, and the software for fitting the PEG standard curve and nonlinear fitting of the corresponding pore size distribution function was Matlab.

Citation Information

Patent Citations

  • Hollow fiber membrane for blood treatment and production method for said hollow fiber membrane for blood treatment

    CN105142693A

  • Test method of aperture distribution of hemodialysis membrane

    CN106596376A